Synthesis, structures and photoluminescence of Zinc(II), cadmium(II), and mercury(II) coordination polymers constructed from two novel tetrapyridyl ligands - Zeng, F.; Ni, J.; Wang, Q.; Ding, Y.; Ng, S.W.; Zhu, W.; Xie, Y. (American Chemical Society, 2010)
Self-assembly of N,N,N',N'-tetra(4-pyridy1)- 1,4-phenylenediamine (L(1)) and N,N-di(2-pyridyl)-N',N'-di(4-pyridy1)-1,4-phenylenediamine (L(2)) with MX(2) (M = Zn, Cd, and Hg; X = Cl. Br, and I) generated novel supramolecular structures with a rich structural diversity. In the crystal of L(1), all pyridyl rings are involved in intermolecular pi center dot center dot center dot pi stacking and T-shaped C-H center dot center dot center dot pi interactions to form a two-dimensional (2D) network. [CdL(1)Cl(2)](n)center dot nH(2)O (4), [CdL(1)I(2)](n) (6), [HgL(1)Cl(2)](n) (7), [HgL(1)Br(2)](n) (8), [Cd(4)(L(2))(4)Cl(8)](n)center dot 2nDMF (13), [CdL(2)Br(2)](n) (14). [CdL(2)I(2)](n) (15), and [HgL(2)Cl(2)](n)center dot 0.5nDMF (16) are coordination polymers. In complex 4, L(1) utilizes all its pyridyl nitrogens to coordinate with Cd(II) centers to afford an unprecedented three-dimensional (3D) binodal (3,4)-connected network with the Schlafli symbol of(8.10(2))(2)(8(4).10(2)). Complexes 6, 7, 8, 14, and IS have zigzag or centipedelike 11) coordination structures. For complex 13, each Cd has an octahedral coordination environment, and the Cd centers are linked by dichloro-bridges to form interesting infinite (CdCl(2))(infinity) chains, which are further bridged by L(2) ligands to form a 2D coordination network. Crystal of 16 has a one-dimensional (ID) chain structure. The chains are arranged in an alternate up-down-up mode, with all the pyridyl rings involved in pi center dot center dot center dot pi stacking interactions to afford a 3D structure which consists of hexagonal channels along the c-axis. [Hg(2)(L(2))(2)Br(4)]center dot H(2)O (17) and [Hg(2)(L(2))(2)I(4)]center dot H(2)O (18) have binuclear coordination moieties, which are linked with water molecules by hydrogen bonds to form ID structures. From these results, it is demonstrated that the structures of the complexes and the coordination modes of L(1) zinc L(2) are strongly dependent on the metal cations and the anions. The Hg(11) atoms in these complexes have tetrahedral coordination environments, whereas the Cd(II) centers have octahedral coordination geometries when Cl(-) is used as the anion, affording 3D and 2D coordination networks. The photoluminescence of L(1), L(2,) and the complexes measured in the solid stale at room temperature indicated that the emission colors vary from violet to yellow, and the emission intensity varies to a large extent, which can be rationalized by the contribution of a conflicting coordination effect and the heavy atom effect.